2013
DOI: 10.1038/nm.3294
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between hypoxia and insulin signaling through Phd3 regulates hepatic glucose and lipid metabolism and ameliorates diabetes

Abstract: Signaling initiated by hypoxia and insulin powerfully alters cellular metabolism. The protein stability of hypoxia-inducible factor-1 alpha (Hif-1α) and Hif-2α is regulated by three prolyl hydroxylase domain–containing protein isoforms (Phd1, Phd2 and Phd3). Insulin receptor substrate-2 (Irs2) is a critical mediator of the anabolic effects of insulin, and its decreased expression contributes to the pathophysiology of insulin resistance and diabetes1. Although Hif regulates many metabolic pathways2, it is unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
125
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 25 publications
12
125
5
Order By: Relevance
“…Increased expression of the Hif-2a target Irs2 in the liver of mice with acute hepatic Hif-p4h-3 deletion was accompanied by a decreased Srebp1c expression (26). The present results indicating weak stabilization of Hif2a, increased expression of Irs2, and decreased expression of Srebp1c and its targets Acca and Fas in the Hif-p4h-2 gt/gt liver agree with those data.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Increased expression of the Hif-2a target Irs2 in the liver of mice with acute hepatic Hif-p4h-3 deletion was accompanied by a decreased Srebp1c expression (26). The present results indicating weak stabilization of Hif2a, increased expression of Irs2, and decreased expression of Srebp1c and its targets Acca and Fas in the Hif-p4h-2 gt/gt liver agree with those data.…”
Section: Discussionsupporting
confidence: 91%
“…Extensive liver-specific stabilization of Hif-2a leads to hepatic steatosis (26,28). However, the Hif-p4h-2 gt/gt mice in the present study showed no steatosis but were instead protected against it.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations